Morpho-Physiological, Chlorophyll Fluorescence, and Diffuse Reflectance Spectra Characteristics of Lettuce under the Main Macronutrient Deficiency - Elena V. Kanash; Nadezhda G. Sinyavina; Dmitryi V. Rusakov; Ksenia V. Egorova; Gayane G. Panova; Yuriy V. Chesnokov (Horticulturae, 2023)
The aim of the present work was to assess the physiological state of plants and photosynthetic apparatus activity in lettuce (Lactuca sativa L.) by non-invasive methods (leaf diffuse reflectance spectroscopy and chlorophyll fluorescence) under the deficiency of one of the macronutrients (nitrogen, phosphorus, or potassium). Our experiments assessed the deficiency of each of the macronutrients relative to plants vegetating under optimal nutrition. The used methods showed that the deficiency of macronutrients causes changes in the optical characteristics of lettuce plants (cvs. ‘Vitaminnyi’ and ‘Kokarda’), including a decrease in the chlorophyll content (57% and 51%) and a change in metabolism, which leads to a decrease in the efficiency of light energy conversion in photochemical processes of photosynthesis and an increase in the dissipation of excess light energy (19% and 10%). Linear regression equations, describing the relationship between net productivity and spectral characteristics of diffuse leaf reflectance with high accuracy, have been obtained. Changes in all studied indicators of the physiological state of plants under the influence of macronutrient deficiency are more pronounced at the early stages of development than in later periods, when the first symptoms of aging appear (decrease in ChlRI). The observed differences between lettuce cultivars and their response to nitrogen, phosphorus, or potassium deficiency are non-specific and mainly represent quantitative variation. The method for assessing the spectral characteristics of diffuse reflection of leaves seems to be the most promising for monitoring the physiological status of plants and early detection of nitrogen, phosphorus, or potassium deficiency.